Soekarno’s Consideration About The Unity Of Indonesia With Composing PNI as Staatspartij Years 1945 - Iftitah Dian Humairoh; Bambang Soepeno; Sugiyanto Sugiyanto; Rully Putri Nirmala Puji (JURNAL HISTORICA, 2020)
Sukarno's thinking about unity began in 1926. At that time Indonesia was colonized and there was no great power to against the colonialist. The circumstances have made Sukarno having ideas to unite the three ideologies of Nationalism, Islamism and Marxism. Soekarno argues that the unity of the three idheologies can bring the people of Indonesia to be united towards the independence. Sukarno wanted to unite the people of Indonesia by forming a party pioneer that is PNI Staatspartij. The problems in this research are: (1) how the background of environmental conditions that influence Soekarno's thinking about unity to form the PNI as Staatspartij; (2) how the Soekarno's concept of thoughts about unity to form the PNI as staatspartij; (3) how Soekarno's struggle to create his thoughts on Indonesian unity through PNI staatspartij. Theories and approaches which are used in this research are The Hermeneutic Theory and the sociology of knowledge and anthropology approach . The research method is used historical research method. The conclusion of this research is that Soekarno have ideas to unite the people of Indonesia by forming PNI Staatspartij as a party that contains all of the elements of society. The Soekarno's concept of thoughts about unity with the form of PNI Staatspartij are Pancasila, Democratic Centralism and Nationalist, Religion and Communist (NASAKOM).